A Model for Predicting Diameter of ‘Red Sensation’ Pears - Garriz, Patricia Isabel (2015)
The pear cultivar ‘Red Sensation’ is showing popularity in the industry, because of its highly-colored, sweet and juicy fruit. Fruit size is critical for marketing pear; therefore, knowledge of growth dynamics becomes essential to program harvesting with minimum losses of size and flavor. The objective of this work was to develop a model to predict the seasonal growth for ‘Red Sensation’ pears, expressed in terms of fruit diameter as a function of time from full bloom. Fruit growth was followed at the Experimental Farm of the Universidad Nacional del Comahue, High Valley region, Río Negro, Argentina (38°56’S; 67°59’W), located in an arid region, with average annual rainfall of 250 mm, on a sandy loam soil, during the 2005-06, 2006-07, 2008-09, 2009-10 and 2010-11 growing seasons. The orchard was irrigated by surface flooding, and cultural practices were performed according to the local standard program. Trees were selected at random, and maximum fruit diameter (FD) measurements were carried out every two weeks with a Vernier caliper. The range of sampling dates was 19 and 117 days after full bloom (DFB). Equations were developed with SYSTAT procedure. The R2 values and residual mean squares were used to evaluate the goodness-to-fit of the models. Results showed that the following logistic model provided the most satisfactory fit to the pooled data (n=695), as compared to the power and linear equations: FD (mm)= 81.49/(1 + e1.9865-0.0301 DFB), R2=0.92, P<0.001. Fruit maximal absolute growth rate, derived from the selected function, was 0.61 mm/day. A prediction chart was based on the development of the equation and showed ‘Red Sensation’ pear sizes, at various times after 112 DFB, with practical application to aid crop marketing. This model can also be used for planning orchard practices such as thinning and irrigation.